Evolution of pitch angle-distributed megaelectron Volt electrons during each phase of the geomagnetic storm - Veenadhari, B. (My University, 2019)
Using Relativistic Electron Proton Telescope measurements onboard Van Allen Probes, the evolution of electron pitch angle distributions (PADs) during the different phases of magnetic storms is studied. Electron fluxes are sorted in terms of storm phase, L value, energy, and magnetic local time (MLT) sectors for 55 magnetic storms from October 2012 through May 2017. To understand the potential mechanisms for the evolution of electron PADs, we fit PADs to a sinusoidal function J0sinn(𝛼eq), where 𝛼eq is the equatorial pitch angle and n is a real number. The major inferences from our study are (i) at L∼5, the prestorm electron PADs are nearly isotropic (n∼0), which evolves differently in different MLT sectors during the main phase subsequently recovering back to nearly isotropic distribution type during the storm recovery phase; (ii) for E ≤ 3.4 MeV, the main phase electron PADs become more pancake like on the dayside with high n values (>3), while it becomes more flattop to butterfly like on the nightside, (iii) at L = 5, magnetic field strength during the storm main phase enhances during the daytime and decreases during the nighttime. (iv) Conversely, at L ∼3, the electron PADs neither respond significantly to the different phase of the magnetic storm nor reflect any MLT dependence. (v) Main phase, electron fluxes with E <4.2 MeV shows a persistent 90◦ maximum PAD with n ranging between 0 and 2, while for E ≥ 4.2 MeV the distribution appears flattop and butterfly like. Our study shows that the relativistic electron PADs depend upon the geomagnetic storm phase and possible underlying mechanisms are discussed in this paper.
Keywords: MAGNETIC FIELD, SPACE WEATHER, Geomagnetic storm